PHOTOCHEMISTRY OF FLUOROQUINOLONES: A REVIEW - Rahila Bano (Baqai Journal of Health Sciences, 2024)
Fluoroquinolone antibiotics are widely used in the treatment of various infectious diseases in humans and animals. These compounds are sensitive to light and undergo photodegradation in the solid and liquid state to form a number of products which have been identified by chromatographic and spectroscopic methods. The fluoroquinolones in aqueous and organic solvents are degraded on exposure to UV and sunlight by a number of pathways depending on the reaction conditions including medium, wavelength and intensity of light and duration of exposure of the solution. The present review deals with the identification of the photoproducts, photodegradation pathways and mechanism of photodegradation of various fluoroquinolones